Jual Beli Buket Uang Perspektif Hukum Islam - Ansori, Muhammad Annas; Fuad, Nurul; Nasrullah, Aan (Lembaga Pendidikan Tinggi Nahdlatul Ulama (LPT NU) PCNU Kabupaten Nganjuk, 2024)
This research aims to analyze the practice of buying and selling money bouquets at Alfia Bouquet, Kediri Regency and reviewing its conformity with Islamic law. Money bouquets, the creation of strings of money in the form of a bouquet, are increasingly in demand among young people. This research uses a qualitative descriptive method with a literature review design. The research results show that buying and selling cash bouquets at Alfia Bouquet Kediri can be done via social media or directly at the point of sale. This transaction uses an ijarah contract, where the buyer selects the desired item and the seller clarifies the product details and payment procedures. Payment can be made in advance with a down payment, directly when the goods are delivered, or via transfer. Even though it involves three transaction models: the buyer gives money for the bouquet, the seller includes money in the bouquet with a fee based on the number of pieces, and a blended fee, this practice is considered in accordance with sharia principles. Although there are concerns regarding usury and waste, as well as regulations, these transactions are generally considered halal because what is traded is the bouquet as a commodity, not the currency itself.